Antena Mikrostrip Patch Square Double Slit Metode Proximity Couple Untuk Teknologi 5G - Waridhah, Sunilam; Marini, Sri; Bakri, Muhammad Amin (Program Studi Teknik Elektro Fakultas Teknik Universitas Islam 45 Bekasi, 2020)
Fifth generation (5G) cellular communication system needs more require higher data rate. One of the major innovations in 5G system is to utilize the millimeter wave (mm-wave) spectrum above 24 GHz together with a beam-controlled phased array antenna. This study aims to design a microstrip antenna with a working frequency of 24.25 GHz- 27.5 GHz with a bandwidth of 3.25 GHz. The patch used is a square double slit and given a U-shaped slot that can change the parameter value, the proximity coupled rationing method with an impedance value (ZL) of 50 Ohms. This microstrip antenna design uses double side PCB RTD Duroid 5880 series dielectric material. The selection of RT Duroid 5880 has a thickness of 1.575 mm, and the dielectric constant value of 2.2 as a substrate is considered suitable for high frequencies (above 10 GHz). The conductor material uses copper with a thickness of 0.035 mm. This study produces dimensional simulation before and after optimization of the working frequency of 26 GHz. Before optimization, the return loss value was -6,625 dB, VSWR 2.7481 and gain 5 dBi. Once optimal, the resulting loss value is -15,821 dB, VSWR 1.3861 and a gain value of 10.1 dBi. Antenna that has been manufactured, is implemented on wifi modem, where the modem The manufactured antenna is implemented on a Wi-Fi modem, where the modem specifications are in 4G. Antenna 5G installed on a wifi modem is still proven to be connected and can be used to access the internet. but the 5G antenna that is attached to the wifi modem can still be connected and can be used to access the internet.